Analysis of the Speed Adjusting Ability with Field Weakening of Rotor  Structure of Permanent Magnet Synchronous Motor for Electric Vehicle - WEN Jia-bin; GUO Han; JING Chao; LIU Jin-hui (Journal of Harbin University of Science and Technology)
The Vtype permanent magnet synchronous motor with iron bridge segment is proposed as the driving motor for electric vehicle. This kind of motor needs to have big torque output in the lowspeed region, as well as widespeed adjusting range with field weakening in the highspeed constant power regionBy analyzing and comparing the influence of different rotor magnetic circuit structure on the main parameters of motor running characteristics, we conclude that：the combination of nonuniform air gap, Vshaped iron bridge segmented permanent magnet, and the change of adjacent magnetic pole spacing improve the noload air gap magnetic tight waveform, increase the motor constant power area of the widespeed adjusting range with field weakening, and satisfy the requirement of large torque output in low speed zoneIn this study, a builtin permanent magnet synchronous motor is designed to drive a 20kW electric vehicle, and the performance of the motor is evaluated by finite element method